A Quantitative Study of Right Dislocation in Cantonese Spoken Discourse. (December 2017) - Lai, Christy Choi-Ting; Law, Sam-Po; Kong, Anthony Pak-Hin
Right Dislocation (RD) has been suggested to be a focus marking device carrying an affective function motivated by limited planning time in conversation. The current study investigated the effects of genre type, planning load and affective function on the use of RD in Cantonese monologues. Discourse data were extracted from a recently developed corpus of oral narratives in Cantonese Chinese containing language samples from 144 native Cantonese speakers evenly distributed in age, education levels and gender. Three genre types representing different structures, styles and degrees of topic familiarity were chosen for an RD analysis: procedural description, story-telling and recount of personal event. The results revealed that genre types and planning load influenced the rate of RD occurrence. (1) Specifically, the lowest proportion of RD occurred in procedural description, assumed to be the most structured genre; whereas the highest rate was found in personal event recount, considered to be the most stylized and less structured genre. (2) The highest proportion of RD appeared near the end of a narrative, where heavier cognitive load is demanded compared with the beginning of a narrative; moreover, RD also tended to co-occur with disfluency. (3) There was a high percentage of RD tokens in the personal event recount for expressing explicit emotions; and (4) a lower rate of occurrence of RD was found in monologues than previous studies based on conversations. The overall findings suggest that the use of RD is sensitive to genre structure and style, as well as planning load effects.